2013
DOI: 10.1016/j.ijome.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study of the interaction between two marine current turbines

Abstract: Abstract-The understanding of interaction effects between marine energy converters represents the next step in the research process that should eventually lead to the deployment of such devices. Although some a priori considerations have been suggested recently, very few real condition studies have been carried out concerning this issue.We therefore ran trials on 1/30 th scale models of three-bladed marine current turbine prototypes in a flume tank. Our work focuses on the case where a turbine is placed at dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 15 publications
8
64
3
1
Order By: Relevance
“…Recently, an experiment has been conducted by Mycek and co-workers (same research team as with Maganga) to study the effects on wake created by an upstream HAMCT towards a downstream HAMCT by using two 1/30th scale horizontal-axis turbines [97]. The experimental results were similar to those obtained by their previous work [93] and those of Bahaj's team.…”
Section: Wake Of Marine Current Turbinesupporting
confidence: 70%
“…Recently, an experiment has been conducted by Mycek and co-workers (same research team as with Maganga) to study the effects on wake created by an upstream HAMCT towards a downstream HAMCT by using two 1/30th scale horizontal-axis turbines [97]. The experimental results were similar to those obtained by their previous work [93] and those of Bahaj's team.…”
Section: Wake Of Marine Current Turbinesupporting
confidence: 70%
“…But the velocity deficit reported by Mycek et al [23] is significantly lower than reported by Chamorro & Porté-Agel [22]. The integral length scales are not reported, but it seems likely that the high-intensity case of [23] will have large length scales, whereas the low-intensity case will have small length scales due to the flow straighteners used to achieve low intensities. The wind tunnel experiments of [22] are likely to have small integral length scales, as commonly found in wind tunnels.…”
Section: Introductionmentioning
confidence: 77%
“…However, cross-comparing between the different studies shows a large overall variation in the measured velocity deficits. At x/D = 4, the variation in velocity deficit is from ≈ 0.1 [23] to ≈ 0.6 [24] highlighting the sensitivity of the wake to different flow conditions. [23], (c) Myers et al [24], (d) Krogstad & Eriksen [25], (e) Myers & Bahaj [9].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this limited output the results of wake investigation are limited to the decay of the wake, [11], the increase in turbulence intensity, [4], and the change of these under influence of waves, [14]. The actual formation of the wake and large scale transients of the wake with waves as described in 1.1 have not been investigated yet and accounted to be covered by the turbulence intensity = ( ).…”
Section: Literature Reviewmentioning
confidence: 99%